Explantation in Tissue Expander and Direct-to-Implant Reconstruction with Acellular Dermal Matrix: How to Avoid Early Reconstructive Failures. Issue 4 (12th March 2021) - Cohen, Leslie E.; Bogue, Jarrod T.; Jin, Julia; Disa, Joseph J.
Abstract : Background: In the United States, approximately 57, 000 tissue expander/implant-based breast reconstructions are performed each year. Complete submuscular tissue expander coverage affords the best protection against implant exposure but can restrict lower pole expansion. The benefits of using acellular dermal matrix are enticing, but questions remain as to whether or not its presence increases reconstructive failures. The purpose of this study was to investigate predictors of explantation in those patients with acellular dermal matrix reconstructions and to discuss salvage techniques. Methods: An approved retrospective review was conducted of 137 patients undergoing 234 individual breast reconstructions over 4 years performed by a single plastic surgeon (J.D.) at a single institution. Patients who underwent implant-based reconstruction with either immediate placement of a tissue expander that was subsequently exchanged for a permanent implant at a second operation or immediate placement of a permanent implant when indicated were included. Results: One hundred thirty-seven patients who underwent 234 implant-based breast reconstructions using acellular dermal matrix met criteria. There was an overall 23 percent complication rate, including any cellulitis, seroma, skin necrosis, and hematoma formation. Significant preoperative risk factors for any postoperative complication included body mass index greater than 25 kg/m 2 and a history of radiation therapy before acellular dermal matrix placement. Radiation therapy was found to be a significant risk factor for postoperative skin necrosis. Of explantations, many fluid cultures grew Gram-negative bacteria. Conclusions: Skin necrosis is a serious risk factor for explantation in implant-based reconstruction with acellular dermal matrix. The reconstructive surgeon should consider early excision of any skin necrosis as soon as it is identified. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.